Pengaruh Penggunaan Handphone terhadap Hasil Belajar Peserta Didik pada Mata Pelajaran Pendidikan Kewarganegaraan - Setiawati, Setiawati; Atmawati, Yuni (Fakultas Agama Islam Universitas Billfath, 2022)
The development of technology, information and communication at this time has a very big influence on people's lifestyles, especially among students, with the emergence of mobile phones that have sophisticated applications can facilitate the activities of its users. Various features of mobile phones are present today with its function as a connection tool for speech in long distances. Today the mobile world is a world of communication and entertainment with audio, text, images, music, and video. One example of the negative influence of handdphone use is that can reduce student learning outcomes, especially the eyes. In the classes of PKn and PKn, most students are willing to ignore teachers who explain the material just to listen to music and be engrossed in messaging during the learning process on the basis of observation, learning and mobile phone addiction at Yapia Pondok Aren Junior High School. The purpose of this research is to find out how much influence mobile phones have on the learning outcomes of learners. The method used is a quantitative approach with a type of correlation research. The results obtained from this study that thitung = 69,323 and ttabel = 1,657. There is a significant influence between the use of mobile phones on the learning outcomes of learners